Synthesis of γ-Al2O3 nanofibers stabilized Co3O4 nanoparticles as highly active and stable Fischer–Tropsch synthesis catalysts. (15th September 2016) - Liu, Chengchao; Hong, Jingping; Zhang, Yuhua; Zhao, Yanxi; Wang, Li; Wei, Liang; Chen, Sufang; Wang, Guanghui; Li, Jinlin
Graphical abstract: More homogeneous dispersed cobalt nanoparticles and improved reducibility as well as interconnected porous structure lead to much higher catalytic activity, C5+ selectivity and stability on the Cop /Al2 O3 -f catalyst. Highlights: Homogeneous cobalt catalyst was prepared by ultrasonication assisted mixing method. The obtained catalyst shows improved catalyst activity and C5+ selectivity. The obtained catalyst shows improved stability. Abstract: Compared with commercial alumina Al2 O3 -c, alumina nanofibers Al2 O3 -f can improve the activity and selectivity of the impregnated catalysts due to its better cobalt crystallite distribution. Although enhanced cobalt dispersion was observed in alumina nanofiber supported catalyst, a homogeneous Co particle size distribution was difficult to obtain by the conventional incipient wetness impregnation method. Here, we demonstrate an efficiency method to prepare cobalt catalyst supported on γ-Al2 O3 nanofibers with controllable crystallite size distribution. The prepared alumina nanofibers and Co3 O4 nanoparticles was mixed and 'rearranged' successfully by an ultrasonication assisted mixing method. The obtained Cop /Al2 O3 -f catalyst possesses nearly mono-dispersed cobalt nanoparticles, improved reducibility and interconnected porous structure. Accordingly, more active Co 0 sites are generated, and the catalytic activity and C5+ selectivity are markedly improved; the enhanced stability of the catalyst is due to the inhibited mobility of the cobalt crystals over the alumina nanofibers.